Pre-professional practice systematization and its relationship to research skills - Guerra Ayala, Margit Julia; Reynosa Navarro, Enaidy; Durand Gómez, Emma Lourdes; Acero Apaza, Yenny Rosario; Florez Lucana, Apolinar; Callata Quispe, Benigno; Guillén Núñez, María del Pilar Lourdes; Payé Colquehuanca, Roberto; Callejas Torres, Juan Carlos (Frontiers in Education, 2023)
This article presents a study on the systematization of pre-professional practice and aims to outline a theoretical-methodological model based on the Oscar Jara proposal, contributions from Neuroscience and Critical-Complex Thinking; to publicize the results of the evaluation of the systematization processes, their level of efficiency, and their articulation with the research skills in 1,150 students from four universities and a pedagogical institute in Peru; and finally, to socialize the results of the application of the model in experimentation in 289 students of said population. The methodology used descriptive-correlative and experimental designs, with data collection through a virtual survey and an evaluation rubric. The results evidenced the precarious level of systematization and investigative capacity, the relationship between both variables, and the impact of the application of the model in an experimental group. Therefore, expanding spaces during pre-professional practice in institutions is recommended to generate an efficient systematization that guarantees the development of research skills in students and prepares them to carry out their research work.